2014
DOI: 10.1140/epjb/e2014-40613-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Rashba coupling in spin-current of monolayer gapped graphene

Abstract: In the current work we have investigated the influence of the Rashba spin-orbit coupling on spin-current of a single layer gapped graphene. It was shown that the Rashba coupling has a considerable role in generation of the spin-current of vertical spins in mono-layer graphene. The behavior of the spin-current is determined by density of impurities. It was also shown that the spin-current of the system could increase by increasing the Rashba coupling strength and band-gap of the graphene and the sign of the spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…17 Previous theoretical reports suggest a significant role of Rashba coupling in the generation of the spin current of vertical spins in monolayer graphene as the spin current can be increased by raising the Rashba coupling strength, while the sign of the spin current is controllable by the direction of the external bias voltage driving the current. 18 Then, for an infinite graphene with uniform Rashba SOC, the equilibrium spin current is proportional to α 2 , where α is the Rashba strength. 19 Hence, spin current in the spin-FET can be tuned or manipulated by varying the Rashba SOC parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Previous theoretical reports suggest a significant role of Rashba coupling in the generation of the spin current of vertical spins in monolayer graphene as the spin current can be increased by raising the Rashba coupling strength, while the sign of the spin current is controllable by the direction of the external bias voltage driving the current. 18 Then, for an infinite graphene with uniform Rashba SOC, the equilibrium spin current is proportional to α 2 , where α is the Rashba strength. 19 Hence, spin current in the spin-FET can be tuned or manipulated by varying the Rashba SOC parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The previous experiments have demonstrated that the strength of the Rashba field and spin precession rate can be controlled by the gate voltage. ,, The first spintronic device concept that utilized Rashba SOC was a spin field-effect transistor . Previous theoretical reports suggest a significant role of Rashba coupling in the generation of the spin current of vertical spins in monolayer graphene as the spin current can be increased by raising the Rashba coupling strength, while the sign of the spin current is controllable by the direction of the external bias voltage driving the current . Then, for an infinite graphene with uniform Rashba SOC, the equilibrium spin current is proportional to α 2 , where α is the Rashba strength .…”
Section: Introductionmentioning
confidence: 99%
“…The extrinsic or Rashba SOC, however, results from the lack of inversion symmetry due to perpendicular electric fields, substrate effects, chemical doping, or curvature of graphene corrugations and can be responsible for inducing a spin polarization in graphene. [9,10] The influences of intrinsic and Rashba SOCs on the transport properties of graphene monolayer systems have extensively been studied in the recent years [5,6,[11][12][13][14]. For instance, it was shown that spin polarization induced by a charge current can reside in the graphene plane and perpendicular to the electric field while its sign changes by varying the Fermi level through an external gate voltage [11].…”
mentioning
confidence: 99%
“…Spintronics is an emerging field which has aimed at exploiting the spin degree of freedom to construct faster and high-performance low-power nanoscale devices [1]. The discovery of isolated graphene monolayer [2,3], a single layer of carbon atoms, with unique electrical, optical and thermal properties has triggered numerous efforts to achieve graphene-based nanoscale devices [4][5][6][7]. The massless Dirac fermions in ballistic graphene can reflect chirality and linear dispersion relation of graphene around the Dirac points, two inequivalent corners of the first Brillouin zone [8].…”
mentioning
confidence: 99%